2021
DOI: 10.3389/fbioe.2021.772002
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA Malat-1 From MSCs-Derived Extracellular Vesicles Suppresses Inflammation and Cartilage Degradation in Osteoarthritis

Abstract: Purpose: Extracellular Vesicles (EVs) derived from hMSCs, have the potential to alleviate cartilage damage and inflammation. We aimed to explore the effects of EVs derived from lncRNA malat‐1-overexpressing human mesenchymal stem cells (hMSCs) on chondrocytes.Material and Methods: hMSCs-derived Extracellular Vesicles (hMSCs-EVs) were identified by transmission electron microscopy and western blot. We used a Sprague-Dawley (SD) rat model of CollagenaseⅡ-induced osteoarthritis (OA) as well as IL-1β-induced OA ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Exogenous application of MALAT1 in EVs can reduce inflammation and joint degeneration in an experimental model of OA. (69) Together these findings suggest that interventions to increase MALAT1 in multiple tissues may have beneficial effects by sponging miR-34a or suppressing its expression (Fig. 3).…”
Section: Discussionmentioning
confidence: 84%
“…Exogenous application of MALAT1 in EVs can reduce inflammation and joint degeneration in an experimental model of OA. (69) Together these findings suggest that interventions to increase MALAT1 in multiple tissues may have beneficial effects by sponging miR-34a or suppressing its expression (Fig. 3).…”
Section: Discussionmentioning
confidence: 84%
“…Zhang and colleagues also reported that targeting lncRNA NEAT1 through artificial exosomes could be one of the options to elevate chondrocyte proliferation for OA treatment ( 196 ). Pan and colleagues confirmed the effect of MALAT1 on chondrocytes, which exhibited a slight cartilage damage and a smooth surface after intra-articular injection of LAMAT1 extracellular vesicles in OA animal model ( 179 ). In addition, the use of nanoparticles as an effective delivery vehicle for targeting lncRNAs provides a new therapeutic strategy owing to improved stability, biocompatibility, and high-dose therapeutic payloads ( 197 ).…”
Section: Targeting Lncrnas: a Novel Treatment Strategy For Oa?mentioning
confidence: 84%
“…Overexpression of MALAT1 in human chondrocytes inhibited cells viability and promoted cartilage ECM degradation through targeting miR145 ( 35 ). Also, lncRNA MALAT1 overexpression in human C28/I2 chondrocyte cells was proved to promote chondrocyte migration, inflammation suppression, and ECM degradation ( 179 ). Besides, MALAT1 could act as sponges for other miRNAs, like miR127-5p ( 36 ), miR150-5p ( 180 ) and miR146a ( 181 ), thus likely to play some regulatory roles in OA cartilage.…”
Section: Biological Functions Of Lncrnas In Oa Pathogenesismentioning
confidence: 99%
“…In addition, as we suggested above, the lncRNA MALAT1 appears to have an important role in OA. MALAT1 in chondrocytes promotes chondrocyte proliferation, suppress chondrocyte apoptosis and reduces extracellular matrix degradation (29,30). Recently, the use of Revesratrol to suppress the activation of MALAT1 showed a decreased of pro-inflammatory genes (NF-κB1 and IL-6) by modulating a microRNA (miR-9) (31).…”
Section: Discussionmentioning
confidence: 99%